Pengaruh Gaya Kepemimpinan, Motivasi Kerja Dan Disiplin Terhadap Kinerja Karyawan (Studi Kasus Pada PT. CITRA GAYA NUSANTARA, Jakarta Selatan) - Nur, Mochamad; Kuncoro, Aris Wahyu (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This research aims to find out the influence of leadership style, work motivation, and discipline on employee performance at PT Citra Gaya Nusantara. This research uses Non Probability Sampling Technique with Saturated Sampling method. The sample in this study is 40 employees and the sample used is 40 respondents calculated using the Slovin formula. Data analysis using multiple linear regression using SPSS software version 22. The results of this study show that the variables of leadership style and discipline have a significant effect on employee performance, while work motivation does not affect employee performance. The results of this research are expected to improve employee performance at PT Citra Gaya Nusantara.